The Bagani spirit through the moral imagination of the Philippine army officers strengthening military leadership based on the Agyu epic - Ebrada, Sandra Cruz (Quezon City Tri-College, University of the Philippines Diliman, 2018)
"Through Moral Imagination, this study looked into Manobo warrior leadership as a source of strengthening military leadership. Four Philippine Army officers, two captains and two Majors, read the Manobo epic, Agyu. The Moral Imagination as a method involved a process where it is grounded on a personal and cultural reality of the officers.Images and feelings were evoked as the story was read. Moral was defined as something better beyond what already exists be it an idea or behavior. Moreover, the process was artistic and thus, nonlinear. It had a mediating role that brought about the possibility that imaginative products or something new is created in the end. The following themes came out of their imaginative narrations: warrior leadership; comparison on soldiers and Bagani traits and behaviors; strategies on war; the roles of women; and highlights of the Manobo culture. These themes a were analyzed based on the Bagani spirit concept. Thus, as part of wisdom and characteristics of a leader, warrior leadership was imagined vis-à-vis military leadership. This included the leader as a fighter and the role of women in the military. The care and responsibilities of a leader imagined the care pf the soldiers' families, of reflecting on Manobo and military relations, and of having peace with the enemy. The concepts of sanctity of the leadership position and the power a leader holds in his position were not discussed by the participants. Recommendations encourage the military to consider Agyu as a leader worthy of emulation; use the Agyu epic as a source of leadership wisdom in military trainings; greatly improve Manobo and military relations; develop a program to study military relations with all indigenous peoples; have better care for the soldiers' families and deliberate further the expanded role of women in the military."-- Author
Thesis (Doctor of Philosophy in Philippine Studies)--University of the Philippines Diliman
Keywords: Epic literature, Philippine; Folk literature, Philippine; Indigenous peoples -- History, Military